Cover Picture: Lipid Technology 2/2016. Issue 2 (February 2016) - Unknown
Abstract : The United States produces enough menhaden oil annually that it could supply the recommended quantities of EPA and DHA to all Americans over 55 who have coronary heart disease; plus supply all pregnant and lactating women in the U.S. with recommended weekly servings of farm‐raised salmon; and still have enough oil left to supply 8 to 12 ounces of salmon per week to an additional 6 to 13 million individuals. Further information can be found in the article by Douglas M. Bibus on page33 .